STRUCTURED EVENT LOG DATA ENTRY FROM OPERATOR REVIEWED PROPOSED TEXT PATTERNS (2013)
A method of structured event log data entry. A structured event log data entry algorithm is provided including a text parser which utilizes stored information including a vocabulary for a human operated process defining classes representing structured information including structured events and structured devices, linguistic patterns for plain text analysis, and relationships between the classes. A pattern proposer utilizes stored linking relations establishing links between the classes and the linguistic patterns. An operator in the system records a plain text event log entry describing an event that occurred in the system into a memory accessible by a processor implementing the algorithm. The text parser implements automatic pattern evaluating the log entry for a matching of any portion of any of the linguistic patterns. The pattern proposer presents a proposed structured event log entry including a structured event and/or structured device for the operator to review whenever the matching is successful.